Menuju Integrasi Peng awasan Pupuk Bersubsidi: Sebuah Rancang Bangun Prototipe E-Suplay Chain Management - Sunarto, Hari (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2014)
Misappropiation of subsidized Ã‚Â fertilizer is one Ã‚Â source Ã‚Â of disturbance Ã‚Â factors that may lead to scarcity of fertilizer supply to farmer and ultimately Ã‚Â disturb to national food Ã‚Â security Ã‚Â program. Ã‚Â AlongÃ‚Â with this, Ã‚Â there are many other sources Ã‚Â of disturbance Ã‚Â in achieving Ã‚Â high standard Ã‚Â of key performance indicators, namely, Ã‚Â 6-precision Ã‚Â - precise in fertilizer Ã‚Â types,Ã‚Â Ã‚Â volume, Ã‚Â place, Ã‚Â time, Ã‚Â quality Ã‚Â and Ã‚Â price. Ã‚Â It Ã‚Â is Ã‚Â a Ã‚Â need Ã‚Â to Ã‚Â minimize disturbances by Ã‚Â supervision.Ã‚Â Ã‚Â By Ã‚Â law, Ã‚Â fertilizer and Ã‚Â pestiside Ã‚Â supervisoryÃ‚Â Ã‚Â committees (KP3) at national, Ã‚Â provicialÃ‚Â and district level asigned to supervice Ã‚Â fertilizer acquisition, distributionÃ‚Â Ã‚Â and Ã‚Â usage Ã‚Â by Ã‚Â farmers. Ã‚Â Under Ã‚Â the Ã‚Â frameÃ‚Â of thinking Ã‚Â an Ã‚Â e-supply Ã‚Â chain management and Ã‚Â management control Ã‚Â system,Ã‚Â the KP3 remains Ã‚Â head Ã‚Â on someÃ‚Â issues, among Ã‚Â others Ã‚Â (a) Ã‚Â not Ã‚Â refer to Ã‚Â Regulation Ã‚Â 60/2008 Ã‚Â onÃ‚Â the Ã‚Â System Ã‚Â of Internal Ã‚Â Control Government, Ã‚Â (b) fragmented Ã‚Â business processsesÃ‚Â in reporting, Ã‚Â (c) in this digital age still relies on writtenÃ‚Â (paperworks)Ã‚Â Ã‚Â Ã‚Â reports. Triangulation Ã‚Â research Ã‚Â method Ã‚Â is being used in longitudinal Ã‚Â study at a time span 2008-2013 to identify the real needs of KP3 then to set up Ã‚Â anÃ‚Â Ã‚Â Ã‚Â appropriateÃ‚Â Ã‚Â prototypeÃ‚Â Ã‚Â ofÃ‚Â Ã‚Â application Ã‚Â software. Ã‚Â The Ã‚Â softwareÃ‚Â Ã‚Â integrates Ã‚Â the businessÃ‚Â Ã‚Â processÃ‚Â Ã‚Â amongÃ‚Â Ã‚Â authorities Ã‚Â and Ã‚Â it Ã‚Â works Ã‚Â online, Ã‚Â During Ã‚Â theÃ‚Â Ã‚Â focus Ã‚Â group discussion, Ã‚Â KP3 Ã‚Â appreciated Ã‚Â these Ã‚Â efforts. Ã‚Â Knowingly Ã‚Â finalization Ã‚Â process Ã‚Â is Ã‚Â still long way Ã‚Â to Ã‚Â go, Ã‚Â becauseÃ‚Â Ã‚Â it needs Ã‚Â to Ã‚Â build Ã‚Â informationÃ‚Â technologyÃ‚Â Ã‚Â infrastructure, Ã‚Â protocol management Ã‚Â and Ã‚Â databaseÃ‚Â Ã‚Â support, Ã‚Â among Ã‚Â others, Ã‚Â 4.29 Ã‚Â million Ã‚Â family Ã‚Â farmers Ã‚Â with attributes. Ã‚Â In Ã‚Â the early Ã‚Â stages, Ã‚Â the software Ã‚Â can be used to replace Ã‚Â paper-based Ã‚Â reports with an online electronic Ã‚Â statements Ã‚Â and a simple diviation Ã‚Â analysis.